Knowledge Sharing, Innovation and Firm Performance: Evidence from Turkey - Mesut Doğan; Husna Doğan (Financial Studies, 2020)
The aim of this study is to determine relationship between knowledge sharing, innovation and firm performance. In the current study, a survey was conducted on a total of 150 high-tech companies operating in Istanbul, Ankara and Antalya. In the analysis results, it is seen that innovation speed and quality affect both the operational and financial performance of firms. In other words, as innovation speed and quality increase, so does the operational and financial performance of firms. Another important finding obtained in the current study is that explicit knowledge sharing, and tacit knowledge sharing have a positive effect on firm performance. A high level of innovation encompasses new products, processes or applications in most company activities. As a result, innovation can create a competitive advantage by creating synergy in the activities of companies and encourage creativity.
Keywords: L25; O31; O33; 330; Innovation Speed and Quality; Explicit and Tacit Knowledge Sharing; Firm Performance